The longitudinal development of social and executive functions in late adolescence and early adulthood - Taylor, Sophie J.; Barker, Lynne A.; Heavey, Lisa; McHale, Sue (Frontiers in Behavioral Neuroscience, 2015)
Our earlier work suggests that executive functions and social cognition show protracted development into late adolescence and early adulthood (Taylor, Barker, Heavey and McHale, 2013). However, it remains unknown whether these functions develop linearly or non-linearly corresponding to dynamic changes to white matter density at these age ranges. Executive functions are particularly in demand during the transition to independence and autonomy associated with this age range (Ahmed and Miller, 2011). Previous research examining executive function (Romine and Reynolds, 2005) and social cognition (Dumontheil, Apperly and Blakemore, 2010) in late adolescence has utilised a cross sectional design. The current study employed a longitudinal design with 58 participants aged 17, 18 and 19 years completing social cognition and executive function tasks, Wechsler Abbreviated Scale of Intelligence (Wechsler, 1999), Positive and Negative Affect Schedule (Watson, Clark and Tellegen, 1988) and Hospital Anxiety and Depression Scale (Zigmond and Snaith, 1983) at Time 1 with follow up testing 12 to 16 months later. Inhibition, rule detection, strategy generation and planning executive functions and emotion recognition with dynamic stimuli showed longitudinal development between time points. Self-report empathy and emotion recognition functions using visual static and auditory stimuli were stable by age 17 whereas concept formation declined between time points. The protracted development of some functions may reflect continued brain maturation into late adolescence and early adulthood including synaptic pruning (Sowell, Thompson, Tessner and Toga, 2001) and changes to functional connectivity (Stevens, Kiehl, Pearlson and Calhouln, 2007) and/or environmental change. Clinical implications, such as assessing the effectiveness of rehabilitation following Head Injury, are discussed.